Technological Market Conjuncture: Risk Assessment Commercialization of Intellectual Property - Kosenko, Aleksandra; Pererva, Petro (Theory, Methodology, Practice – Review of Business and Management, 2014)
This paper deals with the determination of the risk assessment process in market conditions using the method of paired comparisons. The most important factors influencing the level of market appeal of intelligent technology are defined and stipulated. Recommendations are made for reducing the impact of risk factors in course of the commercialization of intellectual property.